Respostas

2014-03-09T12:55:49-03:00
A) x²+25=0              a=1 b=0  c=25
Δ=b²-4ac
Δ=0²-4.(1.25)
Δ=0-4.(25)
Δ=-100

x=-b+-√Δ /2.a                           
x= -0 +-√-100/2.1
x= +ou- i10/2

x¹=10i/2= 5i
 x²= -10/2= -5i                         a letra i é para mudar o sinal negativo da raiz negativa



b) X²-2x+5+0        a=1 b= -2 c= 5
Δ=b²-4ac
Δ=2²-4(1.5)
Δ=4-20
Δ= - 16

x=-b+ou -√Δ /2a
x= - (-2)+ou- √-16/2.1
x=2+ou- √-16/2        
x=2+ou-4i/2          simplifica tudo por 2

x¹= 1+2i
x²= 1-2i



1 5 1